Quixotic frescoes : Cervantes and Italian Renaissance art - De Armas, Frederick A., 1945- (Book collections on Project MUSE., 2006)
"Focusing on Don Quixote, Frederick A. de Armas unearths links between Cervantes' text and frescoes, paintings, and sculptures by Italian artists such as Cambiaso, Michelangelo, Raphael, and Titian. His study seeks to re-engage the critics of today by formulating the link between Cervantes and the Renaissance through an interdisciplinary dialogue that establishes a new set of models and predecessors. This dialogue is used to explore a variety of issues in Cervantes including the absence of a single guiding pictorial program, the doubling of archaeological reconstruction, and the use of ekphrasis as allusion, interpolation, and an integral component of the action. Quixotic Frescoes delves into the politics of imitation, self-censorship, religious ideology expressed through the pictorial, as well as the gendering of art as reflected in Cervantes' work. This detailed and exhaustive study is an invaluable contribution to both Hispanic and Renaissance studies"--Provided by publisher.